Considerações sobre o outro e o comum a partir de Tzvetan Todorov: contribuições para a pesquisa educacional - Mörschbächer, Dulce (2018)
The present dissertation is dedicated to investigate which aspects the other and common concepts of the Franco-Bulgarian thinker Tzvetan Todorov can be approached and contribute in the discussions in the interwoven field of education and art. In order to do so, based on the theoretical-methodological route based on the vestige of Walter Benjamin and the example of Todorov, we approach the Todorovian theory and seek, as a materiality of the research, to deal with two examples of the field of art with the purpose of reflecting on how these two cases can be used as echos of our current society, while clashing with the unknown and the different within a society that values the harmonic and so-called "normal". The proposal consists of a reading of the cases under the Todorovian compass, in order to deal with the relations (or non-relations) established to the encounter with the other that presents itself in the form of a noise before a narcissis tic I. In analysis, we point out the possible repercussions that the encounter between these two different can generate, in order to problematize the speeches that touch tolerance; we also punctuate the possible reverberations generated by the arrival of another dissonal in the field of education and art.